Corrosion behavior of Mg–Gd–Zn based alloys in aqueous NaCl solution - A. Srinivasan; C. Blawert; Y. Huang; C.L. Mendis; K.U. Kainer; N. Hort (Journal of Magnesium and Alloys, 2014)
The corrosion behavior of Mg-10Gd–xZn (x = 2, 6 wt.%) alloys in 0.5 wt.% NaCl solution was investigated. Microstructures of both the alloys consisted of (Mg,Zn)3Gd phase and lamellar long period stacking ordered (LPSO) phase. The morphology of the second phase at the grain boundary differed in both alloys: it was a continuous network structure in Mg–10Gd–6Zn, whereas it was relatively discrete in Mg–10Gd–2Zn. The dendrites were finer in size and highly branched in Mg–10Gd–6Zn. The corrosion results indicated that the increase in Zn content increased the corrosion rate in Mg–10Gd–xZn alloys. Micro-galvanic corrosion occurred near the grain boundary in both alloys initially as the grain boundary phase was stable and acted as a cathode, however, filiform corrosion dominated in the later stage, which was facilitated by the LPSO phase in the matrix. Severe micro-galvanic corrosion occurred in Mg–10Gd–6Zn due to the higher volume of second phase. The stability of the second phase at the grain boundary was altered and dissolved after the long immersion times. Probably the NaCl solution chemically reacted with the grain boundary phase and de-stabilized it during the long immersion times, and was removed by the chromic acid used for the corrosion product removal.